STRUKTUR LINGUISTIK BAHASA: FONOLOGI DAN MORFOLOGI - Ashyfa Meisya Rahman; Lia Artika; Vilia Meitriana; Silvina Noviyanti (STKIP Subang, 2026)
This research examines the linguistic structure of language, focusing on phonology and morphology as fundamental components in understanding the function and conveying of meaning in language. Phonology examines the sound system, the process of sound production, and the role of sound in distinguishing meaning, while morphology examines the internal structure of words and the process of their formation. This research uses a qualitative descriptive method, analyzing various linguistic theories to explain the role, relationship, and contribution of phonology and morphology in the study of language and its use. The results show that both are interrelated components and have a significant influence on pronunciation accuracy, vocabulary development, grammatical understanding, and communication effectiveness. This research confirms that mastery of linguistic structure, particularly phonology and morphology, is crucial for language learning, linguistic research, and the development of overall language competence.